Fetching Automatic Authority Data in ILS from Wikidata via OpenRefine - Pal, Anjan; Mukhopadhyay, Parthasarathi (Journal of Information and Knowledge, 2022)
Authority data is vital for effective library and information services. It serves a major purpose in realizing the collocation function of library catalogues and indexes. Unfortunately, however, authority control has been neglected in library catalogues and other bibliographic databases in India. This paper seeks to demonstrate how authority data can be fetched automatically from Wikidata, a sibling project of Wikipedia. For this purpose, the query language SPARQL is required to formulate the names of persons of Indian origin along with their date of birth and place in Wikidata. The collected datasets are processed and implemented as MARC21-based authority data in KOHA, an open-source library management software. The ways in which the library and information science community can use these free, open-source platforms to gather, organize and share data and how they enhance the retrieval efficiency are shown.